The Influence Of ESG Index Values On Company Performance In Asean Countries - Siregar, Fauzan Mahmud; Chalid, Dony Abdul (UNIVED Press, 2026)
This study examines the relationship between Environmental, Social, and Governance (ESG) performance and corporate performance in 198 ASEAN companies, using financial metrics like Tobin's Q, Earnings Per Share (EPS), and the Altman Z-Score. While global research suggests ESG positively impacts corporate performance, the findings for ASEAN companies are mixed. The analysis concludes that ESG performance does not significantly influence overall company performance in the region. However, it finds that the environmental component of ESG reduces company risk. The reasons behind this anomaly are unclear, suggesting a need for further research to understand the dynamics between ESG practices and corporate performance in ASEAN. This research contributes to the growing knowledge on ESG and emphasizes the importance of region-specific studies to assess the broader relevance of global ESG trends.